A DSP-Based Monitor Algorithm for Time-Varying Trajectory and Rotation Speed of Principal States of Polarization - Zhang, Bin; Ji, Chenxi; Zhao, Jiarun; Cui, Nan; Tang, Xianfeng; Zhang, Xiaoguang (2023 Asia Communications and Photonics Conference/2023 International Photonics and Optoelectronics Meetings (ACP/POEM), 2023)
We propose a DSP-based algorithm for monitoring PSP trajectories and rotation speeds. By using sliding-window median-filtering and modulus judgment method, the algorithm can precisely recover the PSP trajectories and determine the rotation speeds more accurately.